Insights from morphological investigations and molecular phylogenetics reveal a new synonymy in Bellevalia (Asparagaceae: Scilloideae) in Iran - Abdollahi, Mohammad Reza; Bӧhnert Tim; Weigend, Maximilian; Zarre, Shahin (Phytotaxa, 2025)
Bellevalia with 19 recognized species in Iran, is an important geophytic genus within the Iranian flora that is poorly understood regarding intraspecific variation in morphological characters, taxonomy, and phylogeny. We initiated morphological analyses of its species using both herbarium specimens and field samples in preparation of a monographic study of this genus. The present paper focuses on the variability of B. decolorans and its relationship with B. shiraziana. These two species are generally recognized as distinct, but we find that the morphological differences used to distinguish them—such as broadly ovate leaves, longer pedicels, and varying capsule shapes in B. decolorans—are too minor and variable to warrant recognition as distinct species. The differences in capsule and fruit shapes reflect ontogenetic variation within a single species. Our molecular phylogenetic analysis, utilizing nrDNA ITS and cpDNA rps16 sequences, confirms the placement of B. shiraziana within sect. Bellevalia and the close relationship to B. decolorans. Although sequencing the ITS region proved challenging in Bellevalia, the rps16 marker appears to be an effective tool for elucidating interspecific relationships within the genus. Ultimately, we conclude that B. shiraziana should be treated as a synonym of B. decolorans.